Access to drinking water, environmental protection and intestinal parasites in pediatric patients from the neighborhood El Codito in Bogotá, Colombia (2019)
Objective To establish the correlation between intestinal parasitism in children younger than 6 years old and their dwelling in environmental protected areas without aqueduct service, in the neighborhood El Codito, in Bogotá, Colombia. Materials and Methods A cross-sectional study was done with 144 children between the ages of 4 and 70 months. Socio-demographic data were collected by surveying parents, and fecal samples were taken from the children to identify parasites. Descriptive measures were calculated for the variables by population type (parasitized and non-parasitized), establishing significant differences. Using a binary multivariate logistic regression, the correlation between intestinal parasitism and aqueduct was determined, adjusting the other studied variables. Results The prevalence of intestinal parasitism was 38.9%. The lack of aqueduct service was associated with intestinal parasitism (OR=31.25) after adjusting for other studied variables, which included affiliation to the subsidized health insurance regime compared with the contributory regime (OR= 1.49), home pets (OR= 2.58), mothers with professional jobs compared to mothers with non-professional jobs (OR=0.05), and dwelling in a rented room when compared with own dwelling (OR= 6.62). Conclusions Children under the age of 6 living in protected areas without water service were more likely to suffer from intestinal parasitism. It is known that preserving protected areas to protect the environment is of great importance, but if the settlement of populations in these territories is not prevented in time, the population living there is subject to adverse conditions which violate human dignity. © 2019, Universidad Nacional de Colombia. All rights reserved.